Utilization of Stem Bark and Leaves of Kluwih (Artocarpus Altilis Park) as an Anti-Mosquito Repellent: A Case Study of Total Mosquito Mortality (Anopheles Sp) - Kurniawan, Betta; Puspita, Laila; Kurnia, Yogi; Husna, Ismalia; Rahmat, Ali; Umam, Rofiqul; Andriana, Bibin B.; Jermsittiparsert, Kittisak (Universitas Pendidikan Indonesia, 2020)
The purpose of this study was to demonstrate an alternative solution as an insecticide from Indonesian natural ingredients. We investigated the potential use of Artocarpus altilis park (known as kluwih plants in Indonesia) for an anti-mosquito repellent because it contains flavonoids and saponins. The use of this type of insecticide is harmless, inexpensive, and largely available in Indonesia. In the experiment, we extracted bark and leaves of kluwih to obtain insecticidal material to repel Anopheles sp. To ensure the precise extraction and insecticidial effect, the experiments were conducted four times with three repetitions. For each experiment, we used 8.4 mL with the concentrations of 20, 30, and 40% of flavonoid. The results showed that the higher the concentrations of bark and leaf extracts of Artocarpus altilis park the higher the mortality rate of Anopheles sp is.